LOCAL LANGUAGE MAINTENANCE IN TRANSLATING ENGLISH TEXT - Havid Ardi (STKIP PGRI Jombang, 2018)
Translation and foreign language mostly influence the use of local language di Indonesia. However, in the translation text entitled